Production network positions, innovation orientation and environmental dynamics: an empirical analysis of Chinese firms. (1st December 2014) - Wu, Xiaobo; Dou, Wei; Du, Jian; Jiang, Yuanlin
In recent years, local Chinese firms have begun to join global production networks and leverage their local network to enlarge their manufacturing industry. As Chinese firms expand their production networks, their performance may improve due to their innovative use of such networks to diffuse information/knowledge. However, a survey of 171 Chinese firms found that simultaneously pursuing both central and intermediate network positions creates conflict even though both positions positively affect performance. Innovation orientation and environmental dynamics are the areas in which network position affects performance. In highly dynamic environments and for firms with innovation orientations, an intermediate position can improve performance. Conversely, central positions can improve performance for high innovation orientations in less dynamic environments. These results indicate that firms should consider the fitness of the various network positions, innovation strategies and environmental dynamics when expanding their production networks.